The Global Cancer Genomics Consortium's Second Annual Symposium: Genomics Medicine in Cancer Research - Kumar, R; Horvath, A; Mazumder, R; Toi, M; Sato, F; Pillai, MR; Costa, L; Carmo-Fonseca, M; Knapp, S; Dutt, A; Gupta, S; Badwe, R (2013)
The Second Annual Symposium of the Global Cancer Genomics Consortium (GCGC) was held at the Tata Memorial Center in Mumbai, India, from November 19 to 20, 2012. Founded in late 2010, the GCGC aims to provide a platform for highly productive, collaborative efforts on next-generation cancer research through bridging the latest scientific and technology developments with clinical oncology challenges. This year's presenters brought together highly innovative interdisciplinary views and strategies to meet major challenges in cancer research. The symposium featured 3 major themes: OMICS approaches toward the identification of cancer molecular drivers, single-cell analysis in cancer, and clinical and translational genomics. Each theme was represented in presentations of new findings, with an obvious implication in cross-disciplinary components of OMICs and an overwhelming participation by students. In summary, the GCGC symposium provided a discussion and congregation of the latest advances in basic and translational cancer research and offered the participants with a highly cooperative network environment for future collaboration. © The Author(s) 2013.